Pablo Piccato. A History of Infamy: Crime, Truth, and Justice in Mexico. - Frazer, Chris (American Historical Review, 2018)
A review of the book "A History of Infamy: Crime, Truth, and Justice in Mexico," by Pablo Piccato, is presented.